A survey of salaries and position classification of school librarians in private sectarian schools in Metro Manila - Enciso, Clarita Arcangel; Faderon, Rosalie B.; Pascua-Cruz, Ma. Divina A. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1991)
This study attempts to find out the salaries and position classification of school librarians. It seeks to gather further empirical data about the salaries, monetary and other benefits received. It was conducted among sixty-nine of 106 schools librarians in 105 sectarian private schools in Metro Manila.
The descriptive survey method was used, with the questionnaire serving as the research instrument. Respondents were identified through the Department of Education, Culture and Sports' latest list of private schools in Metro Manila. Stratified random sampling was used to obtain a valid sample. The questionnaire which were given personally to the school librarians were composed of four sections : A - contains respondent's personal data; B - gathers data on the prevailing salaries and fringe benefits; C - gathers information about the chool; D - gathers additional comments about the respondent's salaries. Gathered responses were tabulated and analyzed using frequency counts, percentages, arithmetic mean, and ranking.
The findings show that a significant number of librarians are not yet given faculty status and this affects much the salaries received by them. Furthermore, present position, length of service, higher educational attainment, age, longer professional library work experience are not guarantees for higher remuneration.
Based on the above findings, a significant number of respondents, thirty-six (53.73 percent), received basic salaries below grade 10 (P37,224.00). Nineteen (28.36 percent) received salaries belonging to grades 10, 11 and 12 (P37,224.00-45.552.00). A minimal number of respondents, fourteen (20.9 percent), received salaries above grade 12. Furthermore, sex, educational attainment, number of years in present position cannot assure better salaries.
In this regard, this study strongly recommends a serious study and review of the position titles of school librarians in private sectarian schools. Faculty status with corresponding salaries should be strictly followed for better and brighter future of school librarians as well as the school library service in the country.
Thesis (M.L.S.)--University of the Philippines, Diliman
Typescript.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Job analysis; Librarians--Salaries, pensions, etc.--Philippines--Metro Manila